LEGITIMACY OF THE RESTORATIVE JUSTICE PRINCIPLE IN THE CONTEXT OF CRIMINAL LAW ENFORCEMENT - Sukardi, - (Indonesia Law Review, 2014)
This research reviews the essence of the restorative justice principle as an approach in the settlement of criminal cases, and it aims to provide an overview of the construction of the restorative justice principle in criminal law enforcement. The outcomes of the research indicate that the restorative justice principle has been subject to frequent study in its understanding as an alternative criminal case settlement method, by way of positioning outside the criminal judiciary system. As it turns out in practice, however, it has certain weaknesses, particularly in view of the accountability and legitimacy aspects of its establishment. Therefore, there is a need for a scientific investigation process for the purpose of determining the status of parties involved in a case, as well as for positioning the case concerned. Based on such view, the restorative justice principle appears to be the ideal approach to be applied in the criminal judiciary system.